The effect of crashworthiness parameters for vehicle body - Abdul Aziz, Faieza; S., Shahul (International Journal of Advance Research In Science And Engineering, 2015)
With the modernization and globalization of the world we live in, use of vehicles have become very important. Increasing number of vehicle on the road has led to an increase in accidents. Vehicle safety has become more paramount of an issue than it ever was and vehicle manufacturers strive to make their products safer for its occupants and other road users. One of the most important aspects of vehicle safety is the crashworthiness of the vehicle. Balancing the vehicle design, weight and crashworthiness features has become a dilemma for the safety engineers.This paper would review the core crashworthiness parameters and briefly discuss the effects of those parameters on a vehicle body.